Find a Fossil and “Choose your own Adventure”: Fostering undergraduate discovery of evolution using short presentations - Unger, Shem; Rollins, Mark (International Journal of Educational Innovation and Research, 2024)
Science education university curriculum should foster transformative methods of teaching and learning for science majors, including science communication. Pedagogical methods for increasing student awareness of paleontological fossils present challenges as fossils are often presented as preserved remains with little visualizations or reconstructions of fossils. As part of increasing scientific literacy and increasing confidence in professional development skills, student presentations can provide an avenue for promoting these necessary skills for biology majors. This study reports on a short multi-week activity whereby students A) selected a fossil to investigate, B) completed a one to two slide presentation on their fossil of choice, and C) presented their fossil overview to their peers in a lecture classroom. Post-activity surveys and reflections indicate that students found this activity engaging, a fun method for learning about a large diversity of fossils important to evolution, and finally, enjoyed selecting their own fossil. Therefore, allowing students to present on fossils and the evolutionary story they each tell may have increased engagement, piqued interest, and enabled students to both learn and focus on taxa of interest to them personally. We recommend science educators incorporate short, low risk presentations as a learning tool in biology courses to “bring fossils alive” and increase engagement among biology students by promoting student science communication.